Evaluation and comparison of automated hematology analyzer, flow cytometry, and digital morphology analyzer for monocyte counting. (27th May 2018) - Buoro, S.; Moioli, V.; Seghezzi, M.; Previtali, G.; Alessio, M. G.; Simon Lopez, R.; Ortolani, C.; Ottomano, C.; Lippi, G.
Abstract: Introduction: This study was aimed to evaluate monocyte counts on Sysmex XN‐9000, Sysmex CyFlow Space System, and Sysmex DI60 and compare the performance of these systems with the reference optical microscopy (OM) assessment. Methods: In all, 55 peripheral blood samples, collected in K3 EDTA tubes, were analyzed with XN‐9000, CyFlow System (FlowDiff1 and 2), DI60, and OM. Within‐run imprecision was carried out using normal samples. Data comparison was performed with Passing‐Bablok regression and Bland‐Altman plots. Results: The within‐run imprecision of monocyte count on XN, FlowDiff, OM, and DI60 ranged between 1.9% for FlowDiff 2 and 22.1% for DI60. The Passing‐Bablok regression analysis of absolute count yielded slopes comprised between 0.93 (FlowDiff2 vs DI60) and 1.21 (DI60 vs OM), whereas the intercepts ranged between −0.002 (FlowDiff 1 vs FlowDiff 2) and 0.13 (FlowDiff1 and 2 vs DI60). Bland‐Altman plots in absolute values yielded absolute bias comprised between −0.01 × 10 9 /L (FlowDiff 1 vs FlowDiff 2; DI60 vs OM) and 0.15 × 10 9 (XN‐module vs DI60). Conclusion: The results of this analytical evaluation suggest that flow cytometry generates monocyte counts suitable for routine clinical use. OM or DI60 analysis may be useful for identifying morphologic abnormalities, but does not achieve a satisfactory level of accuracy for enumerating blood cells types such as monocytes, which are usually very low in peripheral blood.